ILLUSION OF CONTROL, BETTER-THEN-AVERAGE, MISCALIBRATION, DESIRABILITY BIAS AND UNREALISTIC OPTIMISM AGAINST OVERCONFIDENCE BEHAVIOR (Case Studies on Semarang Investor in Financial Decision Making) - Kusuma, Carissa; Arfianto, Erman Denny (Diponegoro Journal of Management, 2018)
Overconfidence in investment was a bias that affected investor to be too confident when taking financial decision. Sometimes investors are very confidence getting some information and rejecting other contradictive information that in fact is important to be considered before making any financial decision. Physiologists found that humans had a tendency to rely on to unreasonable believes when making decision. Overconfidence itself affected by cognitive biases such as an illusion of control, better-than-average, miscalibration, desirability bias and unrealistic optimism. This study will take a case study on the investor’s financial decision.           Research population used was investors Semarang. By calculation of sample from Hair et al, this research used 150 investors as respondents. This research used quantitative method by distributing questionnaires. Questionnaire consisted of 30 questions representing the illusion of control, better-than-average, miscalibration, desirability bias and unrealistic optimism as variables in the research.The results shown that illusion of control, better-than-average, miscalibration and desirability bias has a positive and significant effect to the overconfidence related in investor’s financial decisions. Otherwise, unrealistic optimism indicates negative and significant effect on overconfidence behavior.